High piezoelectric properties of Sm2O3 doped Ba0·85Ca0·15Ti0·90Zr0·10O3 ceramics. (2nd January 2016) - Li, Q.; Ma, W.; Ma, J.; Meng, X.; Niu, B.
Abstract : This paper discussed the properties of Sm2 O3 doped Ba0·85 Ca0·15 Ti0·90 Zr0·10 O3 (BCTZ– x Sm) ceramics, which were prepared under the high temperature solid state reaction method. Piezoelectric and dielectric properties were observed from these BCZT– x Sm ceramics later. Results revealed that the addition of Sm2 O3 improved the piezoelectric property of BCZT ceramics significantly while affecting the Curie temperature ( T c ) negatively. The BCZT ceramic with x = 0·2 mol.-% displayed an excellent electrical behaviour with excellent piezoelectric coefficient ( d 33 = 554 pC N − 1 ), planar coupling factor ( K P = 53%), dielectric constant ( ) and dielectric loss (tan δ = 1·8%) when sintered at 1450°C.